Effect of Surgery Start Time on Day of Discharge in Anterior Cervical Discectomy and Fusion Patients. Issue 24 (15th December 2016) - Mayo, Benjamin C.; Massel, Dustin H.; Bohl, Daniel D.; Long, William W.; Modi, Krishna D.; Singh, Kern
Abstract : Study Design: Retrospective cohort. Objective: To compare time to discharge for anterior cervical discectomy and fusions (ACDF) when performed as either a first case versus later surgical start times. Summary of Background Data: ACDF is a commonly performed spinal procedure that typically has a short acute recovery period. With an increasing focus on reducing hospital costs and a shift toward outpatient surgical practices, early patient discharge has become a priority for hospitals and physicians alike. However, the impact of surgery start time on the ability for same-day discharge has not been explored in spine surgery. Methods: A surgical database of patients who underwent ACDF from 2013 to 2015 was reviewed. Patients were stratified into two cohorts: those whose surgery was the first of the day (early cohort), and those who underwent later surgeries. Baseline patient characteristics and perioperative variables were compared between cohorts using Student t test and χ 2 test. Same-day discharge was tested for association with surgical start time using Poisson regression with robust error variance controlling for preoperative variables. Results: A total of 106 patients, divided into early and late cohorts of 60 and 46 patients, respectively, were included in the analysis. There were no significant differences in pre- or perioperative characteristics between cohorts (Table 1 ). Same-day discharge was achieved in 36.8% (n = 39) of all ACDF patients. The later cohort was significantly more likely to require an overnight stay compared with the early cohort (RR = 1.61 ± 0.30; P  = 0.010). Conclusion: Patients undergoing ACDF later in the day are at a higher risk for staying overnight than those who have the first surgery of the day. These results may influence operative scheduling, as performing ACDFs early in the day may result in a greater likelihood of same-day discharge, eliminating the increased resource utilization associated with an overnight hospital stay. Level of Evidence: 4